Improving Social Skills in Children for Effective Team Players — An Action Research - SONI, RASHMI; SAXENA, RITU (THE PRIMARY TEACHER, 2015)
Children with social skills show consideration for the feelings and interests of their peers. They take responsibility for their actions, are able to control themselves, and assert themselves when needed. The present action research illuminates the importance of social behaviour among children and the development of social skills among them to create effective team players. The sample was twenty-five Grade II students (aged between seven and eight years) of an English medium school at Madhapur, Hyderabad. These students were having negative social behaviour and attitude which restricted their social interactions with other children of the classroom, leading to the feeling of groupism. The objective was to enable these children build good social skills to become effective team players. By the end of the academic session, the students demonstrated excellent social skills as team players and their ownership towards their class had improved remarkably.